Determinants of COVID-19 Vaccine Acceptance among Dental Professionals: A Multi-Country Survey - Nassani, Mohammad Zakaria (2022)
Purpose: This study sought to investigate the acceptance rate and associated factors of COVID-19 vaccines among dentists and dental students in seven countries. Material and Methods: A structured questionnaire prepared and guided by the report of the SAGE Working Group on Vaccine Hesitancy was distributed among groups of dentists and dental students in seven countries across four continents. Results: A total of 1527 subjects (850 dentists and 677 dental students) participated in this survey. Although 72.5% of the respondents reported their intention to accept COVID-19 vaccines (dentists: 74.4%, dental students: 70.2%), there was a significant difference in agreement between dentists/dental students across countries; generally, respondents in upper-middle-, and high-income countries (UM-HICs) showed significantly higher acceptance rates compared to those in low- and lower-middle income countries (L-LMICs). Potential predictors of higher vaccine acceptance included being a dentist, being free of comorbidity, being well-informed about COVID-19 vaccines, having better knowledge about COVID-19 complications, having anxiety about COVID-19 infection, having no concerns about the side effects of the produced vaccines and being a resident of an UM-HIC. Conclusion: The results of our survey indicate a relatively good acceptance rate of COVID-19 among the surveyed dentists and dental students. However, dentists and dental students in L-LMICs showed significantly lower vaccine acceptance rates and trust in COVID-19 vaccines compared to their counterparts in UM-HICs. Our results provide important information to policymakers, highlighting the need for implementation of country-specific vaccine promotion strategies, with special focus on L-LMICs.